The Political Psychology of Democratic Citizenship 2009
DOI: 10.1093/acprof:oso/9780195335453.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 4 Shallow Cues With Deep Effects: Trait Judgments From Faces and Voting Decisions

Abstract: This chapter examines the impact of rapid automatic processes in political decision making. Specifically, using a dual-process framework, it argues that individuals assess candidate competence on the basis of facial appearance, and that this can predict the outcomes of both U.S. congressional and gubernatorial elections. These judgments occur quickly, and are largely independent of controlled processes. These findings illustrate the complexity of electoral decision making in complicated information environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 63 publications
3
53
0
Order By: Relevance
“…Consistent with the existence of this trade-off, a range of studies have all found an enhanced preference for masculine and dominant-looking leaders and political candidates in times of threat from outgroups or war (Hall, Goren, Chaiken, & Todorov, 2009;Little, Burriss, Jones, & Roberts, 2007;Little, Roberts, Jones, & DeBruine 2012;Spisak, Dekker, Krüger, & van Vugt, 2012;Spisak, Homan, Grabo, & van Vugt, 2012). In such coalitional "games against people," collective action is vital.…”
Section: Trade-offs In Followership Decisionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with the existence of this trade-off, a range of studies have all found an enhanced preference for masculine and dominant-looking leaders and political candidates in times of threat from outgroups or war (Hall, Goren, Chaiken, & Todorov, 2009;Little, Burriss, Jones, & Roberts, 2007;Little, Roberts, Jones, & DeBruine 2012;Spisak, Dekker, Krüger, & van Vugt, 2012;Spisak, Homan, Grabo, & van Vugt, 2012). In such coalitional "games against people," collective action is vital.…”
Section: Trade-offs In Followership Decisionsmentioning
confidence: 87%
“…Across a series of studies, subjects show greater preferences for a dominant-looking, masculine leader when primed with scenarios involving between-group conflict and war than when primed with scenarios of between-group cooperation and peace (Hall, Goren, Chaiken, & Todorov, 2009;Little, Burriss, Jones, & Roberts, 2007;Spisak, Homan, Grabo, & van Vugt, 2012;Spisak, Dekker, Krüger, & van Vugt, 2012). Consistent with this, anthropological records show how Native American tribes had different chiefs in times of war and peace, respectively (Hoebel, 1954;Price & van Vugt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These inferences occur spontaneously and rapidly (Ballew & Todorov, 2007;Bar, Neta, & Linz, 2006;Rule & Ambady, 2008a; Todorov, Pakrashi, & Oosterhof, in press; Willis & Todorov, 2006). Furthermore, recent evidence suggests that these impressions impact the decisions that people make in a variety of important domains, including mate choice , politics (for reviews of this literature see: Hall, Goren, Chaiken, & Todorov, 2009; Olivola & Todorov, in press), business/finance (Gorn, Jiang, & Johar, 2008;Naylor, 2007;Pope & Sydnor, 2008;Ravina, 2008;Rule & Ambady, 2008b), law/forensic-science (Blair, Judd, & Chapleau, 2004;Eberhardt, Davies, Purdie-Vaughns, & Johnson, 2006; Zarkadi, Wade, & Stewart, in press;Zebrowitz & McDonald, 1991), and the military (Mueller & Mazur, 1996).A crucial question, then, is whether appearance-based inferences are valid forms of social judgment. That is, can we use appearances to determine a target-person's characteristics, or are we being fooled by first impressions?…”
mentioning
confidence: 99%
“…In the context of political elections, not only facial beauty but also perceived competence based on appearance augments electoral success (Hall et al, 2009;Todorov et al, 2005;Sussman et al, 2013). Perceived (appearancebased) competence positively affects the CEO selection and the size of his compensation contract (Graham et al, 2017).…”
Section: Introductionmentioning
confidence: 99%